Asesmen Diagnostik Menggunakan Design Thinking dalam Pembelajaran Bahasa Indonesia di SMP Kabupaten Muaro Jambi - Rustam, Rustam; Karim, Maizar; Saputra, Ade Bayu; Ningsih, Arum Gati; Wini, Lusia Oktri (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2024)
This community service program aims to help teachers make learning designs in the form of diagnostic assessment portfolios that are in accordance with the content and learning phases, contain diagnostic assessment grids, and integrate them with learning outcomes and learner readiness needs. This community service method consists of four stages: (1) preparation, (2) implementation, (3) evaluation, and (4) reflection. In the preparation stage, preparing materials, determining the system for implementing activities, and preparing pre-test and post-test for teacher reflection in designing cognitive diagnostic assessments using Design Thinking in Indonesian language learning. The implementation stage includes counseling and small group practice (peer teaching). Evaluation is done through diagnostic assessment with initial competency test and post-test. The reflection stage produced a portfolio that recorded the entire process and results of the activity. For the Design Thinking Empathize process, 95% of junior high school Indonesian language teachers understand and interpret diagnostic assessment material. Define, 80% of Indonesian language teachers are able to construct the problems experienced by their students. Ideate, 80% of Indonesian language teachers analyze patterns/types of construction of competency ideas experienced by their learners. Prototype, 70% of Indonesian language teachers are able to find and compile a portfolio of diagnostic assessment instruments. Test, 72% of Indonesian language teachers are able to design cognitive diagnostic assessment instruments and non-cognitive diagnostic assessments.ABSTRAKProgram pengabdian masyarakat ini bertujuan untuk membantu guru membuat rancangan pembelajaran dalam bentuk portofolio asesmen diagnostik yang sesuai dengan content dan fase pembelajaran, memuat kisi-kisi asesmen diagnostik, dan mengintegrasikannya dengan capaian pembelajaran dan kebutuhan kesiapan peserta didik. Metode pengabdian kepada masyarakat ini terdiri dari empat tahap: (1) persiapan, (2) pelaksanaan, (3) evaluasi, dan (4) refleksi. Pada tahap persiapan, menyusun materi, menentukan sistem pelaksanaan kegiatan, serta menyiapkan pre-test dan post-test untuk refleksi guru dalam merancang asesmen diagnostik kognitif menggunakan Design Thinking dalam pembelajaran Bahasa Indonesia. Tahap pelaksanaan mencakup penyuluhan dan praktik kelompok kecil (peer teaching). Evaluasi dilakukan melalui asesmen diagnostik dengan uji kompetensi awal dan post-test. Tahap refleksi menghasilkan portofolio yang mencatat seluruh proses dan hasil kegiatan. Untuk proses Design Thinking Empathize, 95%, guru bahasa Indonesia SMP memahami dan menginterpretasikan materi asesmen diagnostik. Define, 80% guru bahasa Indonesia mampu mengkonstruksi permasalahan yang dialami peserta didiknya. Ideate, 80% guru bahasa Indonesia menganalisis pola/tipe konstruksi ide-ide kompetensi yang dialami peserta didiknya. Prototype, 70% guru bahasa Indonesia mampu menemukan dan menyusun portofolio instrumen asesmen diagnostik. Test, 72% guru bahasa Indonesia mampu mendesain instrumen asesmen diagnostik kognitif dan asesmen diagnostik non kognitif.